Analysis of the Colombian Economic Transformation Policy Based on the Incorporation of Science, Technology and Innovation, to Improve the Competitiveness of Colombia between the Years 2010-2014 - Lopez-Arellano, Hernán (2016)
This article aims to describe and analyze the Colombian economic transformation policy, which is based in the improvement of innovation process in institutions, companies and economic clusters. It shows sluggish execution of the Colombian economic transformation policy, the objectives of this policy, and the economic and social challenges the government faced from 2010 to 2014. The authors used a document review process as the main methodology to obtain the key data, information and facts to analyze and describe that period of time.